EFISIENSI PRODUKSI USAHATANI JAMUR TIRAM PUTIH DI KABUPATEN BANDUNG BARAT - Latifa, Nadya Hasna; Rochdiani, Dini; Saidah, Zumi (Universitas Galuh, 2023)
The demand for white oyster mushrooms increases every year because white oyster mushrooms are now one of the commodities that are being favored by the public. However, fluctuating production does not support the increased demand, so they still rely on imports. This study aims to measure the level of production efficiency in white oyster mushroom farming. The sample farmers totaled 80 people and were selected using a simple random sampling method. The data analysis method used is the Cobb-Douglass Stochastic Frontier production function and uses the Frontier 4.1 application. The results showed that technical efficiency (ET), allocative efficiency (EA), and economic efficiency (EE) in white oyster mushroom farming each had a value of 76.8%, 40%, and 30%. In general, white oyster mushroom farmers in West Bandung Regency are technically efficient because the efficiency index is above 0.7 but not allocatively and economically efficient. Seeing that the average value does not exceed 0.8, this can explain why white oyster mushroom farming in West Bandung Regency is likely to experience fluctuations in production.